THE 2008-2009 GLOBAL CRISIS AND ENTREPRENEURIAL ACTIVITY - HALIL D. KAYA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2021)
This paper examines how entrepreneurial activity and the factors associated with entrepreneurial activity have changed after the 2008-2009 Global Financial Crisis. For entrepreneurial activity, we look at new business density and new business registrations. For factors associated with entrepreneurial activity, we look at cost of business start-up procedures, cost to import and export, required number of tax payments, total tax rate, required number of procedures for start-ups, required time for different procedures, credit coverage, and legal rights. Our results show that most categories (i.e. taxes, number of procedures required, time required, credit coverage, and legal rights) improved over our sample period. This shows that countries were showing efforts to make improvements in these areas. The results for costs are mixed. The cost of business start-up procedures improved (i.e. declined), but both the cost to export and cost to import deteriorated (i.e. increased) over the sample period. The increases in cost to export and cost to import might have been due to governments’ actions to protect their own producers. We conclude that while most of the measures had improved during this period, these improvements do not seem to translate into an improvement in the number of new businesses. The results are mixed at best. New business density slightly declined, while new business registrations increased. Overall, our findings indicate that when facing a global economic/financial crisis, government action is essential in preventing the collapse of the small business sector. The timely changes in laws and regulations help protect the entrepreneurial environment